2001
DOI: 10.1111/j.1479-8301.2001.tb00046.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychogeriatric Research: A Conceptual Introduction to Aging and Geriatric Neuroscience

Abstract: Psychogeriatrics (PG) is a multidisciplinary specialty in clinical neuroscience dealing with brain disorders in the elderly population. As any other biomedical field PG has to establish an educational and practical framework in epidemiology, etiopathogenesis, diagnosis, treatment, and social, ethical, and legal issues associated with brain aging and age-related central nervous system disorders. Understanding the molecular basis of aging will help to characterize and differentiate the fundamentals of pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 194 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…Few studies with combination treatments have been reported and most of them are poorly designed. We have also to realize that the vast majority of dementia cases in people older than 75-80% are of a mixed type, in which the cerebrovascular component associated with neurodegeneration can not be therapeutically neglected [8,9,14,26,32,44,128].…”
Section: Therapeutic Optimizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies with combination treatments have been reported and most of them are poorly designed. We have also to realize that the vast majority of dementia cases in people older than 75-80% are of a mixed type, in which the cerebrovascular component associated with neurodegeneration can not be therapeutically neglected [8,9,14,26,32,44,128].…”
Section: Therapeutic Optimizationmentioning
confidence: 99%
“…Mutations in the APP, PS1, PS2, and MAPT genes give rise to well-characterized differential neuropathological and clinical phenotypes of dementia [2,28]. The analysis of genotype-phenotype correlations has also revealed that the presence of the APOE-4 allele in AD, in conjunction with other genes, influences disease onset, brain atrophy, cerebrovascular perfusion, blood pressure, -amyloid deposition, ApoE secretion, lipid metabolism, brain bioelectrical activity, cognition, apoptosis, and treatment outcome [2][3][4][5][6]16,26,32,[43][44][45]. The characterization of phenotypic profiles according to age, cognitive performance (MMSE and ADAS-Cog score), serum ApoE levels, serum lipid levels including cholesterol (CHO), HDL-CHO, LDL-CHO, VLDL-CHO, and triglyceride (TG) levels, as well as serum nitric oxide (NO), -amyloid, and histamine levels, reveals sex-related differences in 25% of the biological parameters and almost no differences (0.24%) when patients are classified as APOE-4(-) and APOE-4(+) carriers, probably indicating that gender-related factors may influence these parametric variables more powerfully than the presence or absence of the APOE-4 allele; in contrast, when patients are classified according to their APOE genotype, dramatic differences emerge among APOE genotypes (>45%), with a clear biological disadvantage in APOE-4/4 carriers who exhibit (i) earlier age of onset, (ii) low ApoE levels, (iii) high CHO and LDL-CHO levels, and (iv) low NO, -amyloid, and histamine levels in blood.…”
Section: Genomicsmentioning
confidence: 99%
See 3 more Smart Citations